Chronic itch: emerging treatments following new research concepts. (15th October 2021) - Misery, Laurent; Brenaut, Emilie; Pierre, Ophélie; Le Garrec, Raphaele; Gouin, Olivier; Lebonvallet, Nicolas; Abasq‐Thomas, Claire; Talagas, Matthieu; Le Gall‐Ianotto, Christelle; Besner‐Morin, Catherine; Fluhr, Joachim W.; Leven, Cyril
Abstract : Until recently, itch pathophysiology was poorly understood and treatments were poorly effective in relieving itch. Current progress in our knowledge of the itch processing, the numerous mediators and receptors involved has led to a large variety of possible therapeutic pathways. Currently, inhibitors of IL‐31, IL‐4/13, NK1 receptors, opioids and cannabinoids, JAK, PDE4 or TRP are the main compounds involved in clinical trials. However, many new targets, such as Mas‐related GPCRs and unexpected new pathways need to be also explored.